2002
DOI: 10.1097/00007632-200203010-00019
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Field of Low Back Pain in Primary Care

Abstract: The Fourth Forum reflected a major shift in the conceptualization of LBP in primary care and an increased emphasis on implementation and dissemination of LBP research findings and clinical guidelines. Although there is a wide array of challenges ahead, the Fourth Forum provided a clear message regarding the need to focus research energies on changing practitioner behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 8 publications
0
48
0
Order By: Relevance
“…An estimation of physical demands by self-reports has been criticised as being inaccurate, especially for the more complex load-bearing activities carried out by employees [67]. Otherwise, it has been shown that workload and occupational physical activity can be reliably assessed by questionnaires and that questionnaires can classify groups with heterogeneous occupational tasks [68][69][70][71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimation of physical demands by self-reports has been criticised as being inaccurate, especially for the more complex load-bearing activities carried out by employees [67]. Otherwise, it has been shown that workload and occupational physical activity can be reliably assessed by questionnaires and that questionnaires can classify groups with heterogeneous occupational tasks [68][69][70][71][72][73][74][75][76].…”
Section: Discussionmentioning
confidence: 99%
“…Although the load of whole body vibrations is considered to be associated with LBP [71][72][73], we excluded this variable because we considered this exertion as an external mechanical force and not as a result of physical activity behaviour, which was the focus of our research. It is generally agreed that the aetiology of back pain is multifactorial [74] and that physical load only partially explains the prevalence of back pain [75]. There is robust evidence that psychological factors are related to future episodes of back pain and its related disability [76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence tells us that the essentials for a successful RTW are reassurance upon the benign condition of LBP, encouragement to return early to normal activity and early support in the workplace facilitating progressive return to normal work [10,25]. Medical reassurance is probably the most cost-effective intervention for minimizing pain-related disability [2]. To do this successfully, health care providers must instil confidence in patients , which necessitates a careful physical examination and the willingness to take the necessary time to confidently reassure the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Content validity is important for providing unique and mutually exclusive categories, and in most studies it has only been partially met as the multi-dimensional biopsychosocial aspects of LBP have not been addressed. It is suggested that a bio-psycho-social approach should be included in classifying LBP patients, to satisfy content validity [13,66].…”
Section: Limitations Of the Current Classification Studiesmentioning
confidence: 99%